The effect of stride length variation on oxygen uptake during distance running - Cavanagh, P. R.; Williams, K. R. (Medicine & Science in Sports & Exercise, 1982)
Ten recreational runners (mean VO2max 64.7 ml . kg-1 . min-1) underwent a 5-d acclimation period to treadmill running at a 7 min . mile-1 pace (3.83 m . s-1) for 30 min each day. During these runs their freely chosen stride lengths were determined and expressed as a percentage of leg length (%LL). On two subsequent testing days stride length was systematically varied over a range of +/- 20% LL about the freely chosen value. O2 uptake was determined by the Douglas Bag method. All subjects exhibited a stride length of which O2 uptake was minimized, although the individual profiles varied considerably. The mean increases in VO2 were 2.6 and 3.4 ml . kg-1 . min-1 at the short- and long-stride length extremes, respectively. During unrestricted running deviations from optimal stride length caused a mean increase in VO2 of 0.2 ml . kg-1 . min-1. The relatively efficient running patterns used by the subjects during unrestricted running indicate either an adaption to the chosen stride length through training or a successful process of energy optimization.